2012
DOI: 10.5688/ajpe76351
|View full text |Cite
|
Sign up to set email alerts
|

Medication Therapy Management Services Provided by Student Pharmacists

Abstract: Objectives. To evaluate the impact of student pharmacists delivering medication therapy management (MTM) services during an elective advanced pharmacy practice experience (APPE). Methods. Student pharmacists provided MTM services at community pharmacy APPE sites, documented their recommendations, and then made follow-up telephone calls to patients to determine the impact of the MTM provided. Students were surveyed about the MTM experience. Results. Forty-seven students provided MTM services to 509 patients ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…Lack of resources and lack of motivation are potential reasons, but these are not unique to pharmacy. 34 One explanation is that pharmacy education research focuses on developing a knowledge base, [35][36][37][38] providing services, 39,40 and mastering skills 41,42 rather than on developing reflective information exchange. Also, reflective activities in pharmacy education may be limited because of a lack of available teaching resources.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of resources and lack of motivation are potential reasons, but these are not unique to pharmacy. 34 One explanation is that pharmacy education research focuses on developing a knowledge base, [35][36][37][38] providing services, 39,40 and mastering skills 41,42 rather than on developing reflective information exchange. Also, reflective activities in pharmacy education may be limited because of a lack of available teaching resources.…”
Section: Introductionmentioning
confidence: 99%
“…One study that evaluated the impact of student pharmacists' ability to intervene on DRPs found 75% of recommendations made to the physician were accepted, while a second study found that only 32% of recommendations were accepted. 23,24 Recommendations were done through the patient or via fax; therefore, lower rates of accepted recommendations were likely a reflection of the indirect communication with physicians. Abdelhalim and Lundquist measured the acceptance rates of recommendations made by students who had direct contact with attending physicians in the primary care setting.…”
Section: Discussionmentioning
confidence: 99%
“…13 Gaining pharmacotherapy knowledge and at the same time applying this knowledge in practice is essential for learning in general and, presumably, also for the development of patient-centered care by pharmacy students. [14][15][16] Therefore, storing pharmacotherapeutic knowledge in combination with the situation in which this knowledge will be applied benefits the speed and quality with which the information is recalled. 17 Therefore, we designed and implemented a self-directed learning to guide pharmacotherapy study which was held in the second semester of the fifth year during the APPE.…”
Section: 3mentioning
confidence: 99%